Innovation networks: problems and prospects (Russian case study); The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Chistyakova N. O. Natalya Olegovna (2017, 2017)
Title screen